Total Synthesis and Anticancer Evaluation of BZR-cotoxin IV - Duengo, Suleman; Hidayat, Ace Tatang; Musa, Weny J. A.; Maharani, Rani (Trends in Sciences, 2024)
Anticancer peptides (ACPs) is a potential alternative for future cancer therapy. ACPs specifically inhibit cancer cells through a non-enzymatic membranolysis mechanism. One potential anticancer peptide worthy of investigation is BZR-cotoxin IV. Currently, research on BZR-cotoxin IV is limited to isolation, making it an interesting area for further development. One approach to developing BZR-cotoxin IV is through chemical synthesis techniques. This compound belongs to the group of cyclodepsipeptides that are naturally produced by the fungus Bipolaris zeicola Race 3. The synthesis of BZR cotoxin IV involves 3 steps: (1) Synthesis of the hydroxy acid precursor by conversion of L-valine amino acid to (2R)-hydroxyisovaleric acid, (2) synthesis of the linear depsipeptide using solid-phase peptide synthesis on 2-chlorotrityl chloride resin and (3) cyclization of the linear depsipeptide using solution phase synthesis to produce the BZR cotoxin IV compound with a purity of 11.7 %. BZR-cotoxin IV was characterized using HR-TOF-MS and 1H and 13C-NMR to validate the desired product. Anticancer activity testing was performed using the Resazurin assay on the HeLa cancer cell line, resulting in an IC50 of 187.50 μg/mL (214.014 μM) categorized as moderate. HIGHLIGHTS The chemical synthesis of BZR-cotoxin IV compounds has not been firstly reported. The synthesis of BZR-cotoxin IV was accomplished through a combination of solid-phase and solution-phase peptide synthesis. The objective was to synthesize and evaluate BZR-cotoxin IV for its cancer properties. GRAPHICAL ABSTRACT